Evidence of low prevalence of mycobacterial lymphadenitis in wild boars (Sus scrofa) in Poland. Issue 1 (December 2017) - Witkowski, Lucjan; Orłowska, Blanka; Rzewuska, Magdalena; Czopowicz, Michał; Welz, Mirosław; Anusz, Krzysztof; Kita, Jerzy
Abstract Mycobacterium spp. andRhodococcus equi are generally regarded as the main causes of lymphadenitis in pigs and wild boars. In Poland, mycobacterial submandibular lymphadenitis was first diagnosed in a wild boar in 2012 butMycobacterium spp. infections are also present in the Polish population of European bison (Bison bonasus ). The prevalence of lymphadenitis in Polish wild boars has been found to 8.4% (95% CI 6.2–11.3%) and it has been proved thatR. equi is not an important cause of purulent lesions in these animals. The current study was carried out to assess the prevalence of mycobacterial lymphadenitis in the Polish wild boar population. Submandibular lymph nodes with purulent lesions collected from 38 wild boars in 2010/2011 and negative forR. equi were included. Calculations based on the hypergeometric approximation were used to determine the probability that at least one positive individual would be detected if the infection had been present at a prevalence greater than or equal to the design prevalence. All 38 samples were negative forMycobacterium spp. [0% (95% CI 0, 9.2%)]. Epidemiological analysis showed that the true prevalence was 95% likely to be lower than 10%. In conclusion, mycobacterial lymphadenitis seems to occur rarely in wild boars in Poland. Due to the presence ofMycobacterium spp. infections in other wildlife, the surveillance of mycobacterial infections in wild animals in Poland remains an important issue.